A study on the relationship between work environment and job performance among employees in KANEKA (Malaysia) Sdn. Bhd. / Umira Syuhada Mohd Izaharuddin - Mohd Izaharuddin, Umira Syuhada (2017)
This research has been conducted to identify the relationship between work environment and job performance among employees in Kaneka (Malaysia) Sdn. Bhd. Work Environment consists two variables which are Physical Work Environment and Fringe Benefit. It focuses on two factors that could give impact to the employee's job performance in Kaneka (Malaysia) Sdn. Bhd. The scopes of this research are focused on 76 number of population. The sample sizes taken are 95 people as referred to the sample size for a given population by Krejcie and Morgan (1970). The sampling techniques used are stratified simple random sampling. To measure the relationship between work environment and job performance, Statistical Package for Social Science (SPPS) is utilized. The sample group (N=76) consisted of male and female employees that have various levels of education. For instance, certificate, SPM, Diploma, Degree, and Master. Besides, there are three of research objective has been conducted. Firstly, to examined the relationship between types of physical work environment and job performance. Secondly, to determine the relationship between types fringe benefits and employee's job performance and lastly analyzed the relationship between work environment and job performance among employees in Kaneka (Malaysia) Sdn. Bhd. According to Evans (1996), the relationship between two variables indicated as moderate relationship. These were shown by the value r=.495, which is more than 0.01. Hence, the hypothesis is accepted. In the end of the report, there are several recommendations suggested by the researcher and for future research. In addition, it can help others in future and establishing approach problems.